1980
DOI: 10.1152/ajpheart.1980.238.5.h675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body hypothermia on transventricular simple-capacitor-discharge defibrillation thresholds

Abstract: In 260 successful transventricular simple capacitor-discharge defibrillations performed on 20 mongrel dogs under conditions of body hypothermia, an overall average peak current threshold of 69.5 mA/g of heart (SD 30.4) was found. This value, when compared by means of the unpaired t test with previous data obtained under conditions of relative normothermia (89.5 mA/g of heart, SD 32.8, 346 defibrillations, 20 dogs) yielded a highly significant difference (P less than 0.1%). When comparing the deviation of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This may be related in part to different experimental designs, modes of defibrillation, degree of hypothermia used, different animal species, and lack of statistics in one study. 23 Our finding of improved initial-shock defibrillation is similar to the findings of Arredondo et al, 24 who showed that body hypothermia reduced the transventricular (ie, open-chest model) defibrillation threshold. Unlike our findings, Tacker et al, 23 in a transthoracic defibrillation canine model, found that the defibrillation threshold energy requirement increased 2.5%/°C decrement of body temperature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This may be related in part to different experimental designs, modes of defibrillation, degree of hypothermia used, different animal species, and lack of statistics in one study. 23 Our finding of improved initial-shock defibrillation is similar to the findings of Arredondo et al, 24 who showed that body hypothermia reduced the transventricular (ie, open-chest model) defibrillation threshold. Unlike our findings, Tacker et al, 23 in a transthoracic defibrillation canine model, found that the defibrillation threshold energy requirement increased 2.5%/°C decrement of body temperature.…”
Section: Discussionsupporting
confidence: 88%
“…Other investigators also examined the effects of hypothermia on defibrillation. 16,23,24 The results of these investigators vary in their ability to demonstrate defibrillation efficacy in the setting of hypothermia. This may be related in part to different experimental designs, modes of defibrillation, degree of hypothermia used, different animal species, and lack of statistics in one study.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained data were analyzed using a statistical package (Cohort software, Costat V6.303) to work out analysis of variance. LSD (least significance difference) test was used to compare the means of all treatments following Snedecor and Cochran [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The normality of the data was determined using the Shapiro-Wilk test (PROC UNIVARIATE). Mortality rates that did not fit a normal distribution were arcsine transformed prior to analyses [40]. The Bonferroni correction was applied to examine differences among treatments (PROC MIXED).…”
Section: Statistical Analysesmentioning
confidence: 99%